Extensão rural e manejo de solos no Baixo Amazonas-PA: perspectivas para sustentabilidade - SERRA, Jozimara dos Santos (Universidade Federal do Oeste do Pará, 2024)
The objective of this paper was to discuss the contributions of rural extension to the management of soil and promotion of sustainable in the context of the Lower Amazonas region, PA. However, the process of operation of most technical assistance in Brazil is almost always related to the technification process of the producers, without considering the social and environmental parameters. The new concept of rural extension with public policies provides advances in the action and planning of alternative methods for agriculture, while demonstrate how soil conservation practices and agroecological soil management can improve soil quality and soil maintenance, reflecting the quality of life of producers. The work methodology was consists of two sequential steps. The first, literature review of relevant topics in the context of rural extension, management of soils and conservation, with a modernizing and agroecological view of the soil and, the second: portrayeds possibilities for the Lower Amazon region and examples of sustainable soil management practices that occur in the region. The results of the review demonstrate how fundamental rural extension is in promoting sustainable management practices, such practices should consider the concepts of soil as a resource and as a way of complementing modernizing management and management agroecological. It is concluded that the perspectives to the region need be more estudieds, because is a challenge to develop connected with the producer thoses sustainable practices.